2012
DOI: 10.1111/j.1551-2916.2012.05099.x
|View full text |Cite
|
Sign up to set email alerts
|

High Speed SPM Applied for Direct Nanoscale Mapping of the Influence of Defects on Ferroelectric Switching Dynamics

Abstract: A high speed variation of Scanning Probe Microscopy with continuous image rates on the order of 1 frame per second is applied to investigate the nucleation and growth of individual ferroelectric domains. Movies of consecutive images directly identify nascent domains and their nucleation times, while tracking their development with time and voltage reveals linear domain growth at lateral velocities near 1 mm/s, even faster for nascent domains. Nanoscale maps of nucleation times and growth velocities indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 153 publications
(164 reference statements)
1
34
0
Order By: Relevance
“…With increasing scans, the piezoresponse gradually shifts to an increasingly positive signal, indicative of negative charges being depopulated from the surface. In ambient conditions, on the other hand, consistent surface charge contrast has been reported for PbTiO 3 thin film during and following grounded tip contact scans, and with PZT and BiFeO 3 over hundreds of consecutive PFM images with a constant tip bias when mapping switching nucleation and growth. Even images of organic ferroelectric films remain constant after more than twenty consecutive scans .…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…With increasing scans, the piezoresponse gradually shifts to an increasingly positive signal, indicative of negative charges being depopulated from the surface. In ambient conditions, on the other hand, consistent surface charge contrast has been reported for PbTiO 3 thin film during and following grounded tip contact scans, and with PZT and BiFeO 3 over hundreds of consecutive PFM images with a constant tip bias when mapping switching nucleation and growth. Even images of organic ferroelectric films remain constant after more than twenty consecutive scans .…”
Section: Resultssupporting
confidence: 56%
“…Beyond the general influence of surface charges and local electric fields caused by a biased or grounded metal tip contacting a BTO surface, the specific influence of lattice or grain boundary defect states on polarization switching can be significant. To investigate such effects, piezoresponse hysteresis loops have long been employed, including measurements at distinct positions, or full hysteresis mapping measurements . A relatively symmetric hysteresis loop is detected for the (100)‐film in ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Piezoresponse force microscopy (PFM) imaging has emerged as an effective characterization tool to directly observe the statics and dynamics of ferroelectric domains at the nanometre scale18192021222324. Each PFM image can be characterized by the phase and amplitude parameters to provide information about the orientation of the domain polarization and the value of the piezoelectric coefficient, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have performed PFM characterization across grain boundaries in epitaxial films on bicrystal substrates. Bicrystal substrates enable properties near grain boundaries with preselected misorientation to be characterized . PFM data recorded across a 24° crystallographic tilt about [001] pc (where pc denotes pseudocubic indices) in BiFeO 3 demonstrated that grain boundaries can attract nearby domain walls and restrict the growth of the energetically preferred polarization direction .…”
Section: Domain Grain Size and Thickness Scaling Effectsmentioning
confidence: 99%